2020
DOI: 10.3390/su12229365
|View full text |Cite
|
Sign up to set email alerts
|

Power Hardware in-the-Loop Testing to Analyze Fault Behavior of Smart Inverters in Distribution Networks

Abstract: Deep penetration of distributed generators have created several stability and operation issues for power systems. In order to address these, inverters with advanced capabilities such as frequency and reactive power support the grid. Known also as Smart Inverters (SIs), these devices are highly dynamic and contribute to the power flow in the system. Notwithstanding their benefits, such dynamic devices are new to distribution networks. Power system operators are very reluctant toward such changes as they may cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The green line represents the active power consumption of the HUT and it can be seen that it is almost negligible. Therefore, the dynamic behavior of the HUT can be simply modelled as a capacitor and using the reactive power value at the standard 230 V rms the default parasitic capacitance is approximated as shown in the following Equation (7).…”
Section: Scenario 2: Closed Loop Phil Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The green line represents the active power consumption of the HUT and it can be seen that it is almost negligible. Therefore, the dynamic behavior of the HUT can be simply modelled as a capacitor and using the reactive power value at the standard 230 V rms the default parasitic capacitance is approximated as shown in the following Equation (7).…”
Section: Scenario 2: Closed Loop Phil Simulationmentioning
confidence: 99%
“…This paper aims to investigate the same and to propose the required adjustments in a bid to improve the components performance. A very recent study by Ustun et al [7] analyzes the behavior of smart inverters during faults. It has also shown that software/hardware adjustments are required to study the inverters dynamics in simulation environments.…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics of the voltage signal of the system are analyzed to detect various unsymmetrical faults. But the techniques used for the detection, classification, and location of faults need to be updated and should be based on modern technology [33]. So, that the power system can easily handle these problems that are making it unstable in operation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several studies on P-HIL for reconfigurable realtime grid emulator in power systems with high penetration of renewable and wideband-frequency grid impedance have been published in literature [13]- [18], only few of them use and analyse the P-HIL as a tool for testing the fault behavior of power converters in distribution networks [16]- [18]. In all these works, particular attention is given to the accuracy and the stability analysis of the P-HIL while emulating symmetrical grid faults [16], [17], while only few results of LVRT testing under asymmetrical grid conditions are provided in [18]. Here is concluded that, neither if the grid emulator is controlled in open loop nor in closed loop, the network asymmetrical voltage dips are generated accurately.…”
Section: Introductionmentioning
confidence: 99%